Psoriasis and Psoriatic Arthritis in ChildhoodPsoriasis and Psoriatic Arthritis in Childhood - Nikolay N. Murashkin; Alexander I. Materikin; Eduard T. Ambarchian; Roman V. Epishev; Leonid A. Opryatin; Roman A. Ivanov; Daria S. Kukoleva; Daria G. Kuptsova; Marina U. Pomazanova ("Paediatrician" Publishers LLC, 2020)
Psoriasis is chronic inflammatory skin disease that can develop at any age. Approximately 20-30% of all patients report about first rashes before the age of 18. Psoriatic arthritis is one of psoriasis comorbid conditions. Its signs can range from mild to extremely severe destructive forms. Arthralgia, joint stiffness and swelling are the most common symptoms. Early psoriatic arthritis treatment onset allows to control joint damage which usually occurs during the first 2 years of the disease. The moderate and severe course of psoriasis and psoriatic arthritis may require systemic therapy, however, there is not much data on the efficacy and toxicity of systemic agents in the pediatric practice. This article provides the review of studies on etanercept efficacy and safety in children with psoriatic arthritis.